MO336RENAL CONTRAST-ENHANCED ULTRASOUND (CEUS) TO EVALUATE EARLY AND CHRONIC MODIFICATIONS OF RENAL PERFUSION AND TO PREDICT RENAL DYSFUNCTION AFTER RENAL ISCHEMIA-REPERFUSION IN MICE. (29th May 2021) - Schleef, Maxime; Baetz, Delphine; Leon, Christelle; Pillot, Bruno; Bidaux, Gabriel; Juillard, Laurent; Guebre-Egziabher, Fitsum; Lemoine, Sandrine
Abstract: Background and Aims: Renal ischemia-reperfusion can lead to acute kidney injury (AKI), increasing the risk of developing chronic kidney disease (CKD) through inflammation and vascular lesions. Serum urea or creatinine level routinely used as diagnostic indices of renal function are always delayed from the onset of the disease. Therefore, we currently lack reliable markers to early detect AKI, especially in animals. We aimed to show that non-invasive renal contrast-enhanced ultrasound (CEUS) could be a reliable tool to assess early and chronic changes of renal perfusion after renal ischemia-reperfusion. Method: Male C57BL6 mice underwent 15 minutes of unilateral renal ischemia by clamping of the left renal vascular pedicle (n = 7), or a sham procedure (n = 3), under inhaled general anesthesia by Sevoflurane. A renal ultrasound was performed on the left ischemic kidney at baseline 1 week before the surgery, then, 20 minutes after reperfusion to assess early modifications of renal perfusion, and 1 month after reperfusion to follow chronic modifications. CEUS was performed in supine position by using a high-resolution ultrasonic imaging system (VEVO 3100 Fujifilm Visualsonics, Toronto, Canada) with a MX550D probe fixed in place with an iron support, ensuring the constant imaging plane throughout acquisition. First, a continuous infusion of microbubbles (VS-11913, Fujifilm Visualsonics, Toronto, Canada) was done through the tail vein, then a high mechanical index burst was given to destroy microbubbles when the contrast enhancement had reached a steady state, and finally, low mechanical-index imaging mode was used until, and 30 sec after the contrast agent concentration reached the plateau. Images were recorded and were analyzed using the "destruction-replenishment" fitting model of the Vevo LAB software (Fujifilm Visualsonics, Toronto, Canada). Renal perfusion was estimated by the total renal Blood Volume (rBV) parameter and was expressed as percentage of the baseline value for each animal. Renal function was also assessed by serum urea concentration 1 month after reperfusion, and the long axis lengths of both the kidneys were measured ex vivo after the mice were euthanized. Results: Renal perfusion of the ischemic kidney measured by CEUS was significantly decreased as soon as 20 minutes of reperfusion compared to baseline (median 28, 8% of baseline value; interquartiles [20, 1 – 69, 8%]). 1 month after reperfusion, renal perfusion recovered partially but was still significantly decreased compared to baseline (median 79, 9% of baseline value; interquartiles [52, 8 – 99, 9%]) (Figure A ). In sham operated mice, renal perfusion did not differ from baseline at 20 minutes or 1 month (p > 0.05). The renal function, assessed by serum urea, was mildly but significantly impaired 1 month after ischemia-reperfusion compared with sham (median serum urea 9, 8 vs. 7, 6 mmol/L) (p = 0.02), and this was consistent with the observed kidney atrophy in the ischemic group when compared to the contralateral kidney (median long axis length 7, 5 vs 10, 8 mm) (p = 0.03). Moreover, the decrease of renal perfusion 20 minutes after reperfusion was significantly correlated with the impairment of renal perfusion 1 month after reperfusion (Pearson r = 0.836, p = 0.005) and with the serum urea level at 1 month (Pearson r = -0.710, p = 0.03) (Figure B-C). Conclusion: Renal CEUS was able to detect early impairment of renal perfusion as soon as 20 minutes after 15 minutes of renal ischemia in mice, and perfusion was still decreased 1 month after reperfusion, compared to baseline. This early impairment of perfusion was correlated with the chronic decrease of renal perfusion and renal function 1 month after reperfusion. This was also associated with a significant kidney atrophy. CEUS is an interesting non-invasive tool to assess renal lesions dynamically after ischemia-reperfusion.